Automated Symbolic Orienting: The Missing Link - Ristic, Jelena; Landry, Mathieu; Kingstone, Alan (Frontiers in Psychology, 2012)
Attention can be controlled either exogenously, driven by the stimulus features, or endogenously, driven by the internal expectancies about events in the environment. Extending this prevailing framework, we recently demonstrated that performance could also be independently controlled by overlearned behaviorally relevant stimuli, like arrows, producing automated effects. Using a difficult target discrimination task within a double cuing paradigm, here we tested whether automated orienting engages selective attention, and if in doing so it draws on its own pool of attentional resources. Our data unequivocally support both possibilities, and indicate that human attention networks are uniquely specialized for processing behaviorally relevant information.